2016
DOI: 10.1007/s12275-016-6254-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of infections with zoonotic and human oral species of Campylobacter

Abstract: Genus Campylobacter has been recognized as a causative bacterial agent of animal and human diseases. Human Campylobacter infections have caused more concern. Campylobacters can be classified into two groups in terms of their original host: zoonotic and human oral species. The major zoonotic species are Campylobacter jejuni and Campylobacter coli, which mostly reside in the intestines of avian species and are transmitted to humans via consumption of contaminated poultry products, thus causing human gastroenteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 118 publications
(117 reference statements)
1
29
0
Order By: Relevance
“…Fn, a relevant oral pathogen was reported in this context . Furthermore, Campylobacter species could play a relevant role . Results of clinical evaluations are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fn, a relevant oral pathogen was reported in this context . Furthermore, Campylobacter species could play a relevant role . Results of clinical evaluations are rare.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Furthermore, Campylobacter species could play a relevant role. 40 Results of clinical evaluations are rare. The only available clinical study comparing IBD and healthy patients regarding subgingival microflora found higher prevalence of opportunistic bacteria, including Pm and Td in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In young children, growth reduction can occur depending on the number and duration of inflammatory diarrheal episodes from Campylobacter spp. infections (MAL‐ED studies) . For the human oral campylobacters C. rectus and C. concisus , less is known about their immune activation properties and diarrheal mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…infections (MAL-ED studies). 42,43 For the human oral campylobacters C. rectus and C. concisus, less is known about their immune activation properties and diarrheal mechanisms. For the emerging pathogen C. concisus, a few studies have revealed its pathogenic potential and reported invasion, inducing a leak flux mechanism in epithelial cell cultures by apoptotic leaks and TJ redistribution of claudin-5, as well as delayed immune activation in patients with C. concisus diarrhea.…”
Section: Sequelae Therapy and Preventionmentioning
confidence: 99%
“…Campylobacter species are zoonotic pathogens [1]. Many animals and birds, particularly broiler chickens, carry Campylobacter asymptomatically and shed the microorganism in their feces [2]. Campylobacter jejuni is the most important species of Campylobacter.…”
Section: Introductionmentioning
confidence: 99%